Teyyam is the Best Tool for Reconstructing the History of North Malabar - M. P. Damodaran (Anthropologist, 2008)
Teyyam, one of the popular folk traditions in North Malabar, Kerala is famous for its vividness and the peoples' passion over it. The gods and goddesses, spirits, heroes and heroines, animals and ancestors are worshipped in the form of teyyam. Such divine powers are worshipped in `special kind' of performance in sacred centers. The devotees and believers, who worship teyyam as god, certainly include all the four varnas of the Hindus. All the performers are akin to Scheduled Castes, the so-called `untouchables'. The magico-religious ritual of North Malabar has attracted me more towards it not because of its wonderful world of fantasy but because of its references on real life actions. Myths and legends are the backbone of teyyam. Each teyyam tells us about his-story, the history of the North Malabar. And all these stories narrate the actions of life. For example, the story and performances of teyyams like Chonnamma, Iepalliteyyam, Kurikkal teyyam, Kuttychathan, Maruthiyodan kurikkal, Muchilottu bagavathi, Pottan teyyam, Palenthayikannan, Pulimaranja thondachan, Vishakandan, Vishnumurthi, etc, express glimpses of peoples' life and culture. Some of them point towards social discriminations, purity and pollution, and practice of untouchability. Kathuvanur veeran and Makka pothi narrate the family life. Teyyam like Kuttychathan, Vishnurmuhi, Muchilottubaghavathi, etc, reveal the economic pursuits of the society. So, over all, teyyam provides a real portrait of socio-political, and economic activities of this area.